EVALUASI PROGRAM PEMBINAAN DAN PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH DI KABUPATEN PONOROGO - Dina Trisiana Iskandar; Sumartono Sumartono; Tjahjanulin Domai (Department of Public Administration, Universitas Negeri Surabaya, 2017)
The purpose of this research is to evaluate implementation of SME development program using CIPP model. This evaluation used qualitative approach method. The context evaluation revealed that the task of Department of Industry, Trade, Cooperative and SMEs Ponorogo Regency. The input evaluation includes: development program, budgets, manpower, conditions of participants and facilities. In the process evaluation, showed that technical training is given more than non-technical. The product evaluation, the objectives program to increase the skills have not been fully optimized, while the growth of new entrepreneur objectives cannot be measured due to lack of training evaluation.